Evaluation of leaf blight and purple seed stain in soybean in Argentina - Lavilla, M. (2021)
Introduction. The Cercospora leaf blight and the purple seed stain are endemic diseases of soy in Argentina. Objective. To evaluate the prevalence, incidence and severity of Cercospora leaf blight and the purple seed stain in Argentina during two consecutive years, 2015 and 2016. Materials and methods. Samples were taken from a total of 132 lots. The evaluation of the prevalence, incidence, and severity of Cercospora leaf blight were carried out in the field in R6. The evaluation of the prevalence and incidence of purple seed stain was carried out in the laboratory. Results. Cercospora leaf blight and purple seed stain were found to be widespread throughout the soybean region of Argentina, with a prevalence of 100 %. In 2015 and 2016, the severity of the leaf blight by Cercospora was statistically lower in the southern pampa region compared to the other regions. The northern region presented the highest severity levels of the Cercospora leaf blight. The incidence of purple seed stain did not have statistical differences between regions and years evaluated. No association was found between the pathometric variables of both diseases. There was no quantitative relationship between the severity of symptoms of Cercospora leaf blight on leaf with the incidence of purple seed stain. Conclusion. Both diseases under study were found widespread in all soybean-producing regions of Argentina.